VISIONARY LEADERSHIP AND THE SELF EFFICACY WITH ORGANIZATIONAL COMMITMENT - Suryadi SYARIF; Lina HERLINA (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2019)
The aims of this study is to identify and analyze the relationship between school principal visionary leadership and teacher’s self-efficacy toward teacher’s organizational commitment. The study used a survey method. Population of 223 teachers, and a sample of 143 teachers. Data collected by questionnaire technique. Data analyzed with correlation and regression techniques. The results showed that: 1) there is a positive and significant relationship between the visionary leadership of the head teacher of the school with organizational commitment; 2) there is a positive and significant relationship between self-efficacy with organizational commitment of teachers; and 3) there is a positive and significant relationship between the visionary leadership of the principal and teacher self-efficacy simultaneously with organizational commitment of teachers. Its impliaction, the teacher organizational commitment can be enhanced through the visionary leadership of the principal and teacher self-efficacy.